Solar Energy : Its Potential and Implementation in Developing Countries - Jayaun Jayaun; Emizatul Aini; Aep Saefullah; Ahmad Fadli (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
Solar energy has emerged as a promising renewable energy source with significant potential to address energy challenges in developing countries. This paper aims to explore the potential and implementation of solar energy in these regions, focusing on both the opportunities and challenges associated with its adoption. A qualitative approach is used, examining case studies and existing literature on solar energy deployment in developing countries. The findings highlight that while solar energy offers a cost-effective and sustainable solution, barriers such as high initial investment, lack of infrastructure, and limited technical knowledge still hinder widespread adoption. The paper emphasizes the importance of supportive government policies, international partnerships, and education to accelerate the implementation of solar energy technologies. The significance of this research lies in providing insights for policymakers and stakeholders to design effective strategies that promote the use of renewable energy in developing countries, ultimately contributing to sustainable development.